Design a monitoring system to measure health hazards through route mapping using air and weather quality - Sayem, Abu Shadad Mohammad; Adit, Md.Shadman Shahriar; Yeamin, Shams; Roza, Md Asif Iqbal (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.